Penggunaan dan penerimaan Bahasa Slanga dalam novel indie di Malaysia / Mohd Syuhaidi Abu Bakar and Nor Syafizza Ahmad Tarmizi - Abu Bakar, Mohd Syuhaidi; Ahmad Tarmizi, Nor Syafizza (2019)
Many researches argue that the use of slangs in novels to have led to cultural shock affecting the religious values, eastern culture and against the sensitivity among locals. To rebut such argument, this research recorded slang used in 5 indie novels (Feminis, One Two Jaga, Walang, Haur; and Lendu) and also analyzed on society's acceptance against the use in these indie novels. This research applied qualitative approached where coding books were used to record numbers of slang used in 5 local indie novels and informants were interviewed in a face to face interview sessions. Data were then analyzed using the Atlas.Ti software. The study found that all five novels have used slang in their creative works however informants of this study have mixed reactions towards the use of slangs in indie novels. Majority of informants does not see the use as damaging. This study has eventually contributed to the works of literature of slang within the production of creative works in Malaysia.